NILAI-NILAI KERUKUNAN DALAM TRADISI LOKAL (Studi Interaksi Kelompok Umat Beragama di Ambarawa, Jawa Tengah) - Sulaiman Sulaiman (Harmoni, 2014)
Religious harmony is present in Ambarawa, Semarang because it is supported by traditional laws and societal culture. Religious harmony is also supported by a sense of togetherness, mutual respect and high levels of tolerance. As a result, this area has never experienced vandalism or bloodshed due to religious disharmony. These values can be seen in the celebration of Eid (lebaran), the culture of sonjo, and the ceremonies of Cheng Beng. Eid is celebrated not only by Muslims but also by Christians and Catholics as well. The culture of Sonjo, a traditional prayer given for the passing of Muslims, is also practiced by Christians, Catholics, and Confucianists. Similarly the Cheng Beng tradition of Confucianism has become a culture of the Chinese community as a whole, not just for the Chinese who practice Confucianism.